Hukum Dana Zakat pada Asnaf fi sabilillah dalam Pembangunan Sekolah - Hidayanti, Sri; Fevireani, R.Octa; Wijaya, Angga; Herliza, Siti (Jurnal Indragiri Penelitian Multidisiplin, 2023)
This research examines the use of zakat funds on Asnaf fi Sabilillah in the context of school development within Islam. The objective of the study is to analyze the legal aspects of zakat fund utilization and explore the positive impacts of zakat in enhancing educational access. A qualitative approach with a descriptive research design was employed. Data was collected through interviews with relevant stakeholders, including zakat managers, administrators of zakat organizations, beneficiaries, and by studying related documents such as literature, fatwas, regulations, financial reports, and documentation of school development projects funded by zakat. The findings indicate that utilizing zakat funds on Asnaf fi Sabilillah for school development is valid and compliant with the principles of Sharia in Islam. The implementation of zakat-funded school development projects has improved educational access for economically disadvantaged communities and enhanced school infrastructure in rural areas. Additionally, community participation and involvement of beneficiaries in zakat fund management have increased the effectiveness of the programs. The recommendations include raising public awareness regarding the significance of zakat in enhancing educational access, fostering partnerships with the private sector to augment funding for school development, and promoting transparent and accountable zakat fund management practices. Furthermore, capacity building for zakat managers and beneficiaries, as well as periodic evaluations and monitoring of zakat-funded school projects, are deemed necessary.